1998
DOI: 10.1103/physrevb.58.8
|View full text |Cite
|
Sign up to set email alerts
|

Jahn-Teller transition ofLiMn2O4studied by x-ray-absorption spectroscopy

Abstract: The valence states and local structure of LiMn 2 O 4 have been investigated in comparison with those of ZnMn 2 O 4 and -MnO 2 by using x-ray-absorption spectroscopy on the Mn K edge, in order to study the Jahn-Teller ͑JT͒ transition in LiMn 2 O 4 at T a ϭ280 K. In the near-edge spectra, a systematic edge shift in accordance with the formal manganese valence was found, confirming the Mn 3ϩ /Mn 4ϩ mixed states in LiMn 2 O 4 . Extended x-ray-absorption fine structure reveals a structural disorder of MnO 6 octahed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 15 publications
7
61
0
3
Order By: Relevance
“…To the best of the authors' knowledge, this study has shown the first experimental evidence of the occurrence of bond-length fluctuations in Mn-bearing spinel-type oxides with an ~90° bridge, although Yamada et al (1979) first suspected that the Fe 4 O 4 heterocubane in magnetite behaves as a molecular polaron. assuming the three-shell model, Yamaguchi et al (1998) reported that the Mn-O bond lengths were 2.23 and 1.92 Å at 300 K in the high-form of LiMn 2 O 4 and the ratio of the lengths remained almost constant over the high-and low-forms in the temperature range 200-370 K. These Mn-O bond lengths agree well with those in the low form at 230 K in the present study. However, the longer Mn-O bond length [2.070(3) Å at 320 K] of the 96g model for the high-form is attenuated from the fully elongated Mn 3+ -O bond (~2.2 Å) in the low form (Fig.…”
Section: Role Of Polarons In the Orthorhombic-cubic Phase Transition supporting
confidence: 81%
See 1 more Smart Citation
“…To the best of the authors' knowledge, this study has shown the first experimental evidence of the occurrence of bond-length fluctuations in Mn-bearing spinel-type oxides with an ~90° bridge, although Yamada et al (1979) first suspected that the Fe 4 O 4 heterocubane in magnetite behaves as a molecular polaron. assuming the three-shell model, Yamaguchi et al (1998) reported that the Mn-O bond lengths were 2.23 and 1.92 Å at 300 K in the high-form of LiMn 2 O 4 and the ratio of the lengths remained almost constant over the high-and low-forms in the temperature range 200-370 K. These Mn-O bond lengths agree well with those in the low form at 230 K in the present study. However, the longer Mn-O bond length [2.070(3) Å at 320 K] of the 96g model for the high-form is attenuated from the fully elongated Mn 3+ -O bond (~2.2 Å) in the low form (Fig.…”
Section: Role Of Polarons In the Orthorhombic-cubic Phase Transition supporting
confidence: 81%
“…However, the longer Mn-O bond length [2.070(3) Å at 320 K] of the 96g model for the high-form is attenuated from the fully elongated Mn 3+ -O bond (~2.2 Å) in the low form (Fig. 3), as well as the longer Mn-O bond length (2.23 Å at 300 K) in the high form reported by Yamaguchi et al (1998). This attenuation appears to arise from the symmetry constraint of the 96g model of Fd3m, which imposes the 4:8 ratio upon the number of longer and shorter Mn-O bonds per two Mn octahedra in LiMn 2 O 4 , though the ratio should be approximately 2:10, as Yamaguchi et al (1998) assumed in their EXAFS study using the three-shell model.…”
Section: Role Of Polarons In the Orthorhombic-cubic Phase Transition mentioning
confidence: 94%
“…It was first reported that below the transition temperature a mixture of tetragonal and cubic phases existed [7,8]. The phase transition was attributed to a long range ordering of the local Jahn -Teller distortion of Mn 3+ O 6 octahedra [9]. Later it was concluded that below the phase transition there is a single phase of orthorhombic symmetry (space group Fddd).…”
Section: Introductionmentioning
confidence: 98%
“…The difference in amplitude is evident for k 3 of Mn 3ϩ , the significant damping suggests the enhancement of local disorder by the Jahn-Teller effect of Mn 3ϩ . [20][21][22][23][24] In addition, the spectrum shapes 3 , ͉F(r)͉, shows a radial atomic distribution-like function in real space about the emitting metal ions ͑Fig. 6͒.…”
Section: Samples With Large Mn Content (Y у 08)-thementioning
confidence: 99%